4Work-family conflict and musculoskeletal disorders among wait staff- results from touristic city Isfahan, Iran - Mahdi Malakoutikhah; Mahdi Sepidarkish; Vali Sarsangi; Seyed Abolfazl Zakerian (Annals of Musculoskeletal Medicine - Peertechz Publications, 2018)
Background: This investigation undertook to corroborate the alarming regions concerning the elements that impact work-family dispute among hotel employees in Isfahan, Iran. Method: Data were composed of wait staff workers of 4 or 5-star (or in some rating First Class and Luxury) hotels, and gathered from 150 people by questionnaire that had three sections: demographic, musculoskeletal disorders and work-family conflict. The statistical analysis was done by running Stata version 13. Result: Among the existing participants, 93 cases were reported having had symptoms in at least a single body region. The prevalence of the12-months of WRMSDs was 74.4% (CI95%: 66.64-82.15). As can be seen, the right ankle and right foot were the most prevalent body region having discomfort or pain 47.24% (CI95%:38.44-56.04). The final findings of our study depicted that the association of both time and strain-based work intervention with musculoskeletal disorders was significant statistically.  Conclusion: work-family conflict as a social stressor, specifically in terms of time and strain can highly impact the development of musculoskeletal disorders.